Upregulation of LRRK2 following traumatic brain injury does not directly phosphorylate Thr175 tau - Donison, Neil; Hintermayer, Matthew; Subramaniam, Maegha; Santandrea, Erin; Volkening, Kathryn; Strong, Michael J. (Frontiers in Cellular Neuroscience, 2023)
Phosphorylated microtubule-associated protein tau (tau) aggregates are a pathological hallmark of various neurodegenerative diseases, including chronic traumatic encephalopathy and amyotrophic lateral sclerosis with cognitive impairment. While there are many residues phosphorylated on tau, phosphorylation of threonine 175 (pThr 175 tau) has been shown to initiate fibril formation in vitro and is present in pathological tau aggregates in vivo. Given this, preventing Thr 175 tau phosphorylation presents a potential approach to reduce fibril formation; however, the kinase(s) acting on Thr 175 are not yet fully defined. Using a single controlled cortical impact rodent model of traumatic brain injury (TBI), which rapidly induces Thr 175 tau phosphorylation, we observed an upregulation and alteration in subcellular localization of leucine-rich repeat kinase 2 (LRRK2), a kinase that has been implicated in tau phosphorylation. LRRK2 upregulation was evident by one-day postinjury and persisted to day ten. The most notable changes were observed in microglia at the site of injury in the cortex. To determine if the appearance of pThr 175 tau was causally related to the upregulation of LRRK2 expression, we examined the ability of LRRK2 to phosphorylate Thr 175 in vitro by co-transfecting 2N4R human WTtau with either LRRK2-WT, constitutively-active LRRK2-G2019S or inactive LRRK2-3XKD. We found no significant difference in the level of pThr 175 tau between the overexpression of LRRK2-WT, -G2019S or -3XKD, suggesting LRRK2 does not phosphorylate tau at Thr 175 . Further, downstream events known to follow Thr 175 phosphorylation and known to be associated with pathological tau fibril formation (pSer 9 -GSK3β and pThr 231 tau induction) also remained unchanged. We conclude that while LRRK2 expression is altered in TBI, it does not contribute directly to pThr 175 tau generation.